Techno-Economic Feasibility Analysis of Rooftop Solar Power Plant Implementation Based on Electricity Consumption Patterns and kWh Export Schemes - I Made Agus Sudiartha; Putu Sugiartawan; Aniek Suryanti Kusuma (Jurnal Krisnadana, 2026)
This study aims to analyze the techno-economic feasibility of implementing rooftop solar power plants based on electricity consumption patterns and kWh export schemes. The data used comes from the Kaggle dataset "Surabaya Electric Consumption by Sector" and is processed using Google Colab. The research method uses a descriptive-comparative quantitative approach through electricity consumption pattern analysis, technical simulation of rooftop solar power plants, and a comparison of 65% and 100% kWh export schemes. The results show that the industrial sector has the highest electricity consumption, followed by households and businesses and hotels. Simulations show that increasing solar power plant capacity increases energy production and kWh exports, but nighttime electricity imports still occur because the system does not use batteries. The 100% export scheme provides better economic feasibility than the 65% export scheme, with more optimal savings, ROI, and payback period. The best scenario is a rooftop solar power plant with a capacity of 12.0 kWp with a 100% export scheme, because it produces the highest technical and economic benefits.